Conversion to laparotomy during laparoscopic hysterectomy: a meta-analysis of prevalence and key risk factors - Luo, Qing; Wang, Yan; Zhang, Xiaoyun (Frontiers in Surgery, 2025)
BackgroundThis meta-analysis aimed to estimate the prevalence and identify risk factors for conversion to laparotomy during laparoscopic hysterectomy (LH) for both benign and malignant gynecologic conditions.MethodsA comprehensive search of PubMed, Embase, and the Cochrane Library was conducted to identify studies published between January 2000 and September 2024. Eligible studies reported the prevalence and risk factors for conversion to laparotomy in patients undergoing LH. Studies were assessed for quality using the Newcastle-Ottawa Scale (NOS), and data were extracted on patient demographics, surgical details, and outcomes. A random-effects model was used to pool prevalence estimates and analyze risk factors. Heterogeneity was assessed using the I2 statistic, and publication bias was evaluated with funnel plots and Egger's test.ResultsA total of 12 studies, encompassing 12,785 patients, were included. The pooled prevalence of conversion to laparotomy was 6% (95% CI, 5%–7%), with significant heterogeneity (I2 = 91.8%, p < 0.001). Conversion rates were higher in patients with malignant conditions (11%; 95% CI, 9%–14%) compared to benign conditions (5%; 95% CI, 4%–6%). Key risk factors included a history of adhesions (OR, 3.13; 95% CI, 1.91–5.11) and higher BMI (OR, 1.20; 95% CI, 1.08–1.34). Protective factors included surgeon experience (OR, 0.22; 95% CI, 0.08–0.59) and high surgeon volume (OR, 0.57; 95% CI, 0.34–0.94).ConclusionsConversion to laparotomy occurs in approximately 6% of LH cases, particularly in patients with malignancy, a history of adhesions, or higher BMI. Surgeon expertise and case volume may reduce the risk, highlighting the importance of preoperative risk assessment.